Investigação dos fatores de risco para câncer de mama na cidade de Santos, SP - Garcia, Adriana (2015)
Breast cancer incidence has been increasing on the last twenty years and it has become the most frequent tumor on female population worldwide. On this same period of time, breast cancer has doubled its incidence and mortality rates in Brazil. Santos metropolitan area has been shown for being among the areas with more breast cancer mortality coefficient on São Paulo State. About the carcinogenesis multifactorial of breast cancer, it is known that individual predisposition, age, gender, reproductive story, hormones factors and life style plays an important role on its definition. Therefore, women exposure to environmental carcinogenesis is, without doubt, a factor that should be under constant investigation. This area cited above always had shown to be inadequate regarding to the management of its industrial waste. The objective of this research was to investigate the risk factors associated with breast cancer from women that are living on Santos city. This is a control-case study that used hospital basic institution for the definition of two samples. The case group are women suffering of breast cancer with a diagnostic represented by C50 of the International Disease Code who were assisted at an oncology center of the town hospital. The control group, selected the same hospital were paired by the same age variable whose women did not have breast cancer. The elective women who took part on this study were chosen through of medical chart and were approached at the waiting room of the oncological clinic. The case group was composed by 43 participants (n=43), while the control group had 46 (n=46). A questionnaire that approached issues related to the risk factor investigated on this study and it was validated in order to guarantee its feasibility. The quantities variables were analyzed in order to obtain the mean values from the central tendencies and from dispersion measures for the research results. It was used analysis for absolute and relative frequencies and logistic regression model in order to identify both possible risk and protection factors associated to breast cancer. All the variable were treated on univariated models and the ones that showed a statistical significance up to twenty percent (20%) were included on multiple models on modules and final model and tha adopted significance level was five percent (5%). Living near to chemical area risk showed as being very significant risk factor for the development of breast cancer (OR 8,14; CI 2.13 ¿ 31,06). Breastfeeding for period of less than twelve months had also shown to be a risk factors (OR 4,16; CI 1,10 ¿ 15,79) while the regular use of calcium and vitamin D supply showed to be a protection (OR 0,23; CI 0,59 ¿ 0,88). This study confirms the hypothesis that the environmental exposure to chemical contaminants found near to the residential location is a risk factor for the development breast cancer and it corroborates with the results found in other studies. Futures studies with the goal of analyzing, in a stratified model, each classified area as a chemical risk on this work would be of great interest, in order to identify their specific environmental contaminants and their relation to breast carcinogens.